The chilean tornado outbreak of may 2019: Synoptic, mesoscale, and historical contexts - Vicencio, José (2021)
In late May 2019, at least seven tornadoes were reported within a 24-h period in southern Chile (western South America, 36°–38°S), including EF1 and EF2 events causing substantial damage to infrastructure, dozens of injuries, and one fatality. Despite anecdotal evidence and chronicles of similar historical events, the threat from tornadoes in Chile was regarded with skepticism until the 2019 outbreak. Herein, we describe the synoptic-scale features instrumental in the development of these tornadic storms, including an extended southwest–northeast trough along the South Pacific, with a large postfrontal instability area. Tornadic storms appear to be embedded in a modestly unstable environment (positive convective available potential energy but less than 1,000 J kg−1) and strong low- and midlevel wind shear, with high near-surface storm-relative helicity values (close to −200 m2 s−2), clearly differing from the Great Plains tornadoes in North America (with highly unstable environments) but resembling cold-season tornadoes previously observed in the midlatitudes of North America, Australia, and Europe. Reanalyzing rainfall and lightning data from the last 10 years, we found that tornadic storms in our region occur associated with locally extreme values of both CAPE and low-level wind shear, where a combination of the two in a low-level vorticity generation parameter appears as a simple first-order discriminant between tornadic and nontornadic environments. Future research should thoroughly examine historical events worldwide to assemble a database of high-shear, low-CAPE midlatitude storms and help improve our understanding of these storms’ underlying physics.